Passive Smoking as a Risk Factor of Dry Eye in Children - Amany Abdel-Fattah El-Shazly; Walid Mohamed Abd El Raouf El-Zawahry; Ahmad Mohamed Hamdy; Manal Basyouni Ahmed (Journal of Ophthalmology)
Purpose. Adult active smoking is a risk factor for dry eye. We hypothesize that passive smoking in children can also produce the same effects. Methods. We included 112 school children presenting with eye discomfort. Assessment of eye dryness and its severity levels depending on symptoms of dry eye, visual symptoms, tear breakup time (TBUT), Schirmer-1 test, and corneal fluorescein staining were done for all of them. Exposure to cigarette smoking was assessed by history-taking and urinary cotinine levels. Results. Dry eye was found in 80/112 children. Passive smoking was documented in 76/112 children. Number of cigarettes to which the child was exposed per day and the duration of exposure to passive smoking were significantly higher in children with dry eye compared to those without. Urinary cotinine, and cotinine/creatinine ratio (CCR) was significantly higher in children with dry eye compared to those without dry eye. Multiregression analysis showed that the most important determinants of dry eye were CCR and number of cigarettes/day. Conclusion. Passive smoking represents a significant risk factor of dry eye in children comparable to that shown with active adult smoking. Male children are more prone to this effect.